2007
DOI: 10.1111/j.1600-0501.2007.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of teeth exhibiting periapical pathology by immediate implants. A prospective, controlled clinical trial

Abstract: It is concluded that for those implants where primary stability was achieved, the immediate implant placement performed at extraction sockets exhibiting periapical pathology did not lead to an increased rate of complications and rendered an equally favorable type of tissue integration of the implants in both groups. Implant placement into such sites can, therefore, be successfully performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
180
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(193 citation statements)
references
References 30 publications
8
180
0
5
Order By: Relevance
“…Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) . Similar success rates have been reported, however, with immediate implant placement whether the site was infected or not, provided infection was controlled thorough debridement of alveolar tissue by curettage and administration of broad-spectrum antibiotics 17,20,31,32,50,55) .…”
Section: Introductionmentioning
confidence: 49%
See 4 more Smart Citations
“…Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) . Similar success rates have been reported, however, with immediate implant placement whether the site was infected or not, provided infection was controlled thorough debridement of alveolar tissue by curettage and administration of broad-spectrum antibiotics 17,20,31,32,50,55) .…”
Section: Introductionmentioning
confidence: 49%
“…Hence, the presence of periapical infection should not be considered as a potential contraindication for immediate implant placement. Furthermore, human clinical studies have reported that implant survival rate ranged from 92 to 100% after 12 to 60 months of follow-up 13,17,20,31,32,50,55) . One study reported that the implant survival rate was 100%, and that hard and soft tissue integration was similar and favorable between the healthy and infected groups 18) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations